2018
DOI: 10.1016/j.imr.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The combination of exercise training and Zataria multiflora supplementation increase serum irisin levels in postmenopausal women

Abstract: BackgroundWe examined the effect of antioxidant supplementation and exercise on irisin within postmenopausal women.MethodsForty-eight participants (age: 55.7 ± 4.9 years; weight: 68.0 ± 6.3 kg; BMI 27.0 ± 2.7; mean ± SD) were randomized into four groups for the eight week intervention: control group (CG; n = 12), resistance training group (RTG; n = 12), supplementation with Zataria multiflora group (ZG; n = 12), or supplementation with Z. multiflora and resistance training group (ZRTG; n = 12). RTG and ZRTG pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…In brief, Brazilian authors applied the same type of resistance training in sedentary women (33-45 years of age) who had a similar body composition status as our participants, and evidenced significant decreases in BF% (from 37% to 31) [51]. Further, similar results were reported in an Australian study with obese women [52], while an Iranian team confirmed the effects of 8-week circuit weight training on body weight reduction in postmenopausal women [53]. On the other hand, the positive effects of 8-week circuit resistance training on body composition were not confirmed in a US study on premenopausal women, although numerical values of BMI and BF indices showed promising trends [52].…”
Section: Positive Effects Of Endurance and Resistance Training On Antsupporting
confidence: 84%
“…In brief, Brazilian authors applied the same type of resistance training in sedentary women (33-45 years of age) who had a similar body composition status as our participants, and evidenced significant decreases in BF% (from 37% to 31) [51]. Further, similar results were reported in an Australian study with obese women [52], while an Iranian team confirmed the effects of 8-week circuit weight training on body weight reduction in postmenopausal women [53]. On the other hand, the positive effects of 8-week circuit resistance training on body composition were not confirmed in a US study on premenopausal women, although numerical values of BMI and BF indices showed promising trends [52].…”
Section: Positive Effects Of Endurance and Resistance Training On Antsupporting
confidence: 84%
“…All participants were aged 18 years or older. Of the included studies, three studies evaluated only men, four studies evaluated only women, and the other two studies did not differentiate between the sex of the participants . Seven out of nine studies had follow‐up periods of 12 (44.4%) and 8 weeks (33.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, for the other two groups, no changes occurred in their BMI level. In this regard, Ercan et al (2017) and Ghanbari-Niaki et al (2018) showed an increased irisin level, which resulted from weight loss after 10 weeks of freewheel running exercise in female mice and eight weeks of resistance training in postmenopausal women, respectively. On the other hand, Boström et al (2012) reported a twofold increase in circulation irisin after 10 weeks of AET in healthy overweight adults.…”
Section: Discussionmentioning
confidence: 97%
“…While a large body of literature exists regarding the effects of chronic exercise training on irisin in adults, the results of many studies have been far from conclusive, and no consensus has been reached. Some studies have shown the potential effects of exercise training on circulating irisin (Boström et al, 2012;Ercan et al, 2017;Ghanbari-Niaki et al, 2018;Kim, So, Choi, Kang, & Song, 2015;Moienneia & Hosseini, 2016;Zhao, Su, Qu, & Dong, 2017) and myostatin (Hinkley, Konopka, Suer, & Harber, 2017;Hittel et al, 2010;Roth et al, 2003;Saremi et al, 2010;Walker, Kambadur, Sharma, & Smith, 2004). While others have shown that irisin (Ellefsen et al, 2014;Hecksteden et al, 2013;Moienneia & Hosseini, 2016;Pekkala et al, 2013) and myostatin (Besse-Patin et al, 2014;Binns, Gray, Henson, & Fort, 2017;Hofmann et al, 2016;Ziaaldini et al, 2015) may not change after long-term exercise training.…”
Section: Introductionmentioning
confidence: 99%